Coups and the consolidation mirage: lessons for stability in new democracies. Issue 7 (2nd October 2020) - Greene, Samuel R.
ABSTRACT: Many recent treatments of democratic consolidation in both the academic and policy realms rely on minimalist understandings of consolidation. Repeated elections are expected to provide sufficient stability to protect nascent democracies from reversal. However, a comparison of unexpected coups in Honduras (2009) and Mali (2012) following political crises, with Ghana and Mongolia, where similar political crises were solved in 2008 within political institutions, demonstrates the limits of such understandings lead to both academics and policymakers to unduly optimistic expectations for stability. In Ghana and Mongolia, political crises were resolved within the context of democratic institutions. However, in both Honduras and Mali, a series of elections failed to lead to democratic consolidation. Military reversal revealed that democracy in both cases rested on fragile institutions that collapsed when subjected to political stress. Instead of minimalist standards for consolidation, both academic and policy study of stability in young democracies should rely on institutional standards for consolidation that take into account institutional performance and the commitment of actors to respect institutions. Absent well-functioning institutions, a cycle of elections should not be expected to prevent the breakdown of democracy and the grave consequences for stability that so frequently accompany such breakdowns.